Reinventing Financial Regulation: A Blueprint for Overcoming Systemic Risk - Persaud, Avinash (Springer, 2015)
Reinventing Financial Regulation offers an analysis of the fundamental flaws that plague the current system of financial regulation, one built around ideas of "risk-sensitivity" and "capital adequacy." Author Avinash Persaud argues that while some sensible reforms have been introduced, a fresh approach—centered on risk capacity—is required. When the entire regime is compromised, simply slapping bandages on each new wound will do nothing to cure the underlying disease.